MODEL OF ORGANIZING DISTANCE LEARNING OF ENGLISH BY FUTURE ECONOMISTS - Bykonia Oksana Pavlivna (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
This article is concerned with describing the model of distance teaching of English to cadets of economic specialties.The main aim of designing this model of distance teaching of English to cadets of economic specialties is mastering English communicative competence. It is mentioned that the English communicative competence consists of linguistic, speech, linguasociocultural, educational and strategic competences at the level of B2.2. The article substantiates the model of distance teaching of English to cadets of economic specialities which they study at the Academy of the State Penitentiary Service. It is emphasized that according to the EducationalProfessional Programme, Educational-Qualification Characteristics, cadets of economic specialties must master English communicative competence for Specific Purposes at the level of B2.2 to use English while communicating in oral and written forms. It is based on a detailed review of psychological, pedagogical and methodological research as to teaching English to students of economic specialties. The organization of distance teaching of English to cadets of economic specialties has been modeled. In the process of creating this model, the following was taken into account: pedagogical and methodological principles on which the model is based; subjects and objects of the study; educational discipline, in which distance learning is taking place; the aim of teaching and learning English; the teachers and cadets’ interaction; regular monitoring of cadets’ learning English at the Academy of the State Penitentiary Service; using various means of communication available to the cadets on the territory of the Academy; an observance of requirements according to the sanitary rules and norms to hold English classes, cadets’ educational activity using technical aids to study English; protection of the cadets’ personal data, calculating the time for the organization of the cadets’ independent extracurricular work; English themes according to the programme of this discipline (with different types of exercises and tasks); the amount of hours for distance learning of English; learning tools and aids; the stage of distance learning; cadets’ control of mastering English communicative competence. The model of organization of distance teaching of English to cadets of economic specialities which is presented. It contains organizational, educational and control stages and provides a way to manage educational activities during students’ distance learning of English